ASIA AND CLIMATE CHAOS (International Journal of Engineering Sciences & Management Research, 2018)
The COP Treaty from 2015 in Paris outlines the plan for global de-carbonisation during this century up to around 2075. However, this is not an achievable objective, because the largest emitters of CO2s are not planning to follow the steps in the COP project, namely the giant Asian countries in East, South East and South Asia. The ever wider set of Asian economic miracles are basically driven by the “take off” strategy (Rostov, 1970) (when poor) or the “catch-up” strategy (Barro, 1991; Barro and Sala-i-Martin, 1992, 1995) (when affluent). Their stated future energy demand surpasses the global de-carbonisation plan.